Méthode et raison dans De la conduite de l’entendement de Locke - Alain Firode (Revue LISA)
The short treatise Of the Conduct of the Understanding (written by Locke in 1697 and published in 1706), sets out a conception of the art of thinking which, in some respects, is original within the intellectual context of the second half of the 17th century. One of the main particular features of this text is the way reason is presented not as an innate and natural faculty but rather as the laboriously acquired, artificial product of the methodical conduct of human understanding. Another striking feature comes in the formative role played in this process of access to rationality by the progressive acquisition of habits and mental automatisms which involve cerebral mechanisms of a corporeal nature. The result is that the Lockean conception of the method supports a non-dualist anthropology which holds the incarnation of the spirit to be an impassable and constituent dimension of human thought. Of the Conduct, then, sets itself apart again by the essentially critical conception of rationality that Locke puts forward. Here reason does not have the appearance of a specific source of knowledge but rather of a “touchstone”, the function of which is limited to testing the knowledge submitted from the exterior.